An Interview with Janet Waldron: Reforming Maine State Government - Waldron, Janet (Maine Policy Review, 1995)
This past year Janet Waldron was appointed Commissioner of the Department of Administrative and Financial Services for the State of Maine, planting her firmly in the center of a number of recent Maine state government reform initiatives. In this interview, Waldron discusses some of these current initiatives and in the process, offers a vision of a more streamlined, responsive, and accountable government.
Keywords: Maine government reform